Synthesis, characterization and thermal behaviour of solid-state 3-methoxybenzoates of heavy trivalent lanthanides and yttrium(III) - Dametto, P. R. [UNESP]; Ambrozini, B. [UNESP]; Siqueira, A. B.; Carvalho, C. T. [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2010)
Solid-state Ln(L)(3) compounds, where Ln stands for trivalent Tb, Dy, Ho, Er, Tm, Yb, Lu and Y, and L is 3-methoxybenzoate, have been synthesized. X-ray powder diffractometry, infrared spectroscopy, complexometry and elemental analysis were used to characterize the compounds. In order to study the thermal behaviour of these compounds simultaneous thermogravimetry and differential thermal analysis (TG-DTA) and differential scanning calorimetry (DSC) were used. The results provided information on the composition, dehydration, polymorphic transformation, thermal stability and thermal decomposition of the synthesized compounds.
Keywords: Characterization; Heavy lanthanides; 3-methoxybenzoate; Thermal behaviour